Demographic change and public education spending : a conflict between young and old? - Ueli Grob; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2005)
Demographic change in industrial countries will influence educational spending in potentially two ways. On the one hand, the decline in the number of school-age children should alleviate the financial pressure. On the other hand, the theoretical/empirical literature has established that the concomitantly increasing proportion of elderly in the population can influence the propensity of politicians to spend on education. Using a panel of the Swiss Cantons for the period from 1990 to 2002, we find that the education system has exhibited little elasticity in adjusting to changes in the school-age population, and that the share of the elderly population has a significantly negative influence on the willingness to spend on public education.
Keywords: H72; J18; I22; 330; public finance; education finance; demographics; panel estimates; Switzerland; Öffentliche Bildungsausgaben; Public Choice; Alternde Bevölkerung; Schätzung; Teilstaat; Schweiz